Dysfunctional Resident Lung Mesenchymal Stem Cells Contribute to Pulmonary Microvascular Remodeling. (1st January 2013) - Chow, Kelsey; Fessel, Joshua P.; Ihida‐Stansbury, Kaori; Schmidt, Eric P.; Gaskill, Christa; Alvarez, Diego; Graham, Brian; Harrison, David G.; Wagner, David H.; Nozik‐Grayck, Eva; West, James D.; Klemm, Dwight J.; et al.
Abstract : Pulmonary vascular remodeling and oxidative stress are common to many adult lung diseases. However, little is known about the relevance of lung mesenchymal stem cells (MSCs) in these processes. We tested the hypothesis that dysfunctional lung MSCs directly participate in remodeling of the microcirculation. We employed a genetic model to deplete extracellular superoxide dismutase (EC‐SOD) in lung MSCs coupled with lineage tracing analysis. We crossed floxp sod3 and mT/mG reporter mice to a strain expressing Cre recombinase under the control of the ABCG2 promoter. We demonstrated In vivo that depletion of EC‐SOD in lung MSCs resulted in their contribution to microvascular remodeling in the smooth muscle actin positive layer. We further characterized lung MSCs to be multipotent vascular precursors, capable of myofibroblast, endothelial and pericyte differentiation in vitro. EC‐SOD deficiency in cultured lung MSCs accelerated proliferation and apoptosis, restricted colony‐forming ability, multilineage differentiation potential and promoted the transition to a contractile phenotype. Further studies correlated cell dysfunction to alterations in canonical Wnt/β‐catenin signaling, which were more evident under conditions of oxidative stress. Our data establish that lung MSCs are a multipotent vascular precursor population, a population which has the capacity to participate in vascular remodeling and their function is likely regulated in part by the Wnt/β‐catenin signaling pathway. These studies highlight an important role for microenviromental regulation of multipotent MSC function as well as their potential to contribute to tissue remodeling.